THE IMPACT OF PROMOTIONAL TOOLS ON CONSUMER BUYING BEHAVIOR AT MATAHARI DEPARTMENT STORE MANADO TOWN SQUARE - Malombeke, Shintia; Saerang, David Paul Elia; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2014)
For maximizing market share, every company will carry out various forms of marketing strategies aimed to boost sales. Promotional activity is one form of marketing strategy that aims to introduce and simultaneously influence consumers to buy the products offered by the company so as to increase the volume of sales. The purpose of this study was to find the impact of promotional tools such as buy one get one free, price discount, coupon promotion and physical surroundings on consumer buying behavior at MDS Manado Town Square. This research is a quantitative research that used associative research. The data was collected through questionnaire with sample size is 75 respondents who are selected often and always purchasing at MDS MTS. The conclusion is there is significant positive impact of buy one get one free, price discount, and coupon promotion on consumer buying behavior and Â no significant at physical surroundings. It means MDS MTS should improve the promotions and the physical surroundings in order to attract more customers to make purchasing. Therefore the researcher recommended to MDS MTS to better continues maintaining and improve their marketing strategies through promotional activities in order to attract more customers to continue making purchases. Keywords: promotional tools, consumer buying behavior